Incidencia de la tipología familiar y relacional en el establecimiento de estilos de apego de niños del municipio del Guamo (2023)
This research aborted the issue of attachment styles developed by nuclear and singleparent families, its general objective is to determine the incidence of family and relational typology in the attachment style in children under one to three years of age in the municipality of Guamo For this, the contributions of the Systemic model and the postulates of John Bowlby were taken into account, a mixed study of a quantitative and qualitative approach was carried out, nonexperimental with a descriptive design of group difference with a correlational scope, through the application of instruments such as a sociodemographic file. For this research, a nonprobabilistic choice method was used for accessibility, there was a sample of twelve families divided into six single-parent families and six nuclear families.